Euthanasia Dalam Perspektif Hukum Pidana Yang Berlaku Di Indonesia - Kasidin, Sunarko; Karsono, Karsono (Faculty of Law Universitas 17 Augustus 1945 Cirebon, 2021)
The purpose of this research is to find out the picture related to euthanasia that occurs and applies in Indonesia. What if, due to technological advances, there is